Dose selection for the investigational anticancer agent alisertib (MLN8237): Pharmacokinetics, pharmacodynamics, and exposure–safety relationships. (18th November 2014) - Venkatakrishnan, Karthik; Zhou, Xiaofei; Ecsedy, Jeffrey; Mould, Diane R.; Liu, Hua; Danaee, Hadi; Fingert, Howard; Kleinfield, Robert; Milton, Ashley
Abstract We report population pharmacokinetic, pharmacodynamic, and pharmacokinetic‐safety analyses to support phase II/III dose/regimen selection of alisertib, a selective Aurora A kinase (AAK) inhibitor. Phase I studies in adult cancer patients evaluated dosing on Days 1–7 in 21‐day cycles or Days 1–21 in 35‐day cycles, with corresponding maximum tolerated doses of 50 mg twice daily (BID) and 50 mg QD, respectively. Population pharmacokinetic analyses supported dose‐ and time‐linear pharmacokinetics without identification of clinically meaningful covariates. Exposure‐related increases in skin mitotic index and decreases in chromosomal alignment/spindle bipolarity in tumor mitotic cells confirmed AAK inhibition. Exposures in the 7‐day schedule at or near 50 mg BID are expected to result in tumor AAK inhibition based on pharmacodynamic assessment in patient tumors. Exposure‐safety analyses of data from patients receiving doses of 5–200 mg/day in the 7‐day schedule support a low (∼7%) predicted incidence of dose‐limiting toxicity at 50 mg BID. Taken together, these analyses support a pharmacologically active and acceptably tolerated dose range of alisertib for future clinical development.